ANALISIS PEMANFAATAN ANGGARAN DANA BOS (BANTUAN OPERASIONAL SEKOLAH) DI SMP NEGERI SE-KECAMATAN KEBUMEN - Wahyuningsih, Sri; Astuti, Desi Widi (P4M STIE Putra Bangsa, 2018)
Operational grant school next abbreviated as BOS is a central government program in providing funding the school fees of the students for a unit of primary and secondary education compulsory nine years. The purpose of this research is to know the influence of human resources students, the time of BOS funds are distributed, and effectiveness of infrastructures on the utilization of budgetary BOS funds. The method that used in this research is the descriptive method with the quantitative approach. Data collection methods used are observation, the literature study, and questionnaire. The data analysis of this research used regression analysis linear multiple by using SPSS version 16. The result of this research shows that from human resources students variable is 0,632 influential not significant impact on the use of the BOS funds. The time of BOS funds are distributed is 0,036 and effectiveness of infrastructures is 0,000 influential in a significant impact on the utilization of budgetary BOS funds. The Problems in this research are lack of knowledge about BOS funds and the distribution of BOS funds that are not timely. The advice that given from this research are: (1) forthe schools should be held socialization about the BOS funds. (2) For the committee of the schools should check the reports that had made by the school. (3) The management of using more improve the quality of the facilities infrastructure in order to support the process teaching.   Keywords : Human resources, the time of BOS  funds distributed, the effectiveness of infrastructures, and utilization of the BOS fund.